4-(Dimethylamino)pyridinium tribromide: whole molecule disorder of cation and anion - Ng, Seik Weng (International Union of Crystallography, 2009)
In the title salt, C(7)H(11)N(2) (+)·Br(3) (−), the cation and the near-linear anion [Br—Br—Br = 179.41 (8)°] both show whole-molecule disorder about crystallographic twofold rotation axes. The cation is weakly hydrogen-bonded to the anion by an N—H⋯Br interaction. The crystal studied was found to be a racemic twin, with a twin component of nearly 50%.